Bad deal - Korman, Susan (Minneapolis : Darby Creek, 2011)
Fish gets himself into trouble after selling his ADHD medication to kids at school.
Accelerated Reader AR
Keywords: Attention-deficit hyperactivity disorder -- Juvenile fiction; Drug dealers -- Juvenile fiction; High schools -- Juvenile fiction; Schools -- Juvenile fiction; Attention-deficit hyperactivity disorder -- Fiction; Drug dealers -- Fiction; High schools -- Fiction; Schools -- Fiction